1988
DOI: 10.1002/cjce.5450660305
|View full text |Cite
|
Sign up to set email alerts
|

Flotation kinetics for titanium, zirconium and bitumen recovery from oilsand tailings

Abstract: The kinetics of heavy mineral and bitumen recovery from oilsand tailings are presented. The results show that the recovery rates for titanium, zirconium and bitumen were affected by addition of surfactants Tretolite F46 and E3453. Recoveries were a function of time and of the minerals and bitumen present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The outcomes of a plot like this are seen in Fig. 4 which are close to those described in air-water systems by Shah et al [38] and Ityokumbul et al [39]. The influence of solid inclusion on the bubble slip velocity in the presence of MIBC frother has also been displayed in Fig.…”
Section: Hydrophilic Silica Slurry Experimentssupporting
confidence: 84%
“…The outcomes of a plot like this are seen in Fig. 4 which are close to those described in air-water systems by Shah et al [38] and Ityokumbul et al [39]. The influence of solid inclusion on the bubble slip velocity in the presence of MIBC frother has also been displayed in Fig.…”
Section: Hydrophilic Silica Slurry Experimentssupporting
confidence: 84%
“…It is known from previous investigations that iron, titanium and zirconium minerals have pronounced tendencies to be concentrated in the tailings streams from processing plants which use the hot water extraction process for recovery of bitumen from tar sands (Trevoy et al, 1978) and that flotation-scavenging of such tailings can further concentrate such heavy minerals (Hall et al, 1983;Hall and Tollefson, 1986;Ityokumbul et al, , 1986Ityokumbul et al, , 1988. In this study, Ca++ and Fe+++ ions such as in calcium chloride (CaCI2.…”
Section: Effects Of Ca++ and Fe+++ On The Flotation Behaviour Of Tailmentioning
confidence: 99%
“…Based on an NBC content of 5.3 mass% of dry tailings solids which are produced at the rate of 2400 tonnedday, it may be calculated that isolation of all the NBC from the centrifuge tailings of an oil sands plant producing 2 1,000 m3/d of synthetic crude could provide an energy source equivalent to approximately 125 tonnes of low grade lignite coal per day. Although it is relatively small quantity to have a major impact, failure to recognize its presence in extraction plant tailings as a part of the combustible organics (Ityokumbul et al, 1988) could lead to misinterpretation from combustion analysis.…”
Section: Properties Of Isolated Nbcmentioning
confidence: 99%
“…Although a great deal of research has been carried out on the application of flotation cells to oil recovery (Angelidou et al, 1977;Takahashi et al, 1979;Strickland, 1980;Sylvester and Byeseda, 1980;Van Ham et al, 1983;Ityokumbul et al, 1988), little work has been done on the application of flotation columns. Moreover, the research done on the flotation cells has been restricted to very dilute emulsions (oil concentrations less than 600 mg/L).…”
Section: Tankmentioning
confidence: 99%
“…The addition of up to 4 percent by weight of sodium chloride resulted in an enhanced performance of the flotation cell. Ityokumbul et al (1988) studied the flotation kinetics of bitumen recovery from oil sand tailings. The results showed that the recovery rate was dependent upon the type of surfactant added to the feed.…”
Section: Tankmentioning
confidence: 99%